A new photodynamic therapy photosensitizer (p1) promotes apoptosis of keloid fibroblasts by targeting caspase-8. Issue 1 (28th February 2023) - Zhang, Ming-Zi; Dong, Xin-Hang; Zhang, Wen-Chao; Pan, De-Li; Ding, Li; Li, Hao-Ran; Zhao, Peng-Xiang; Liu, Meng-Yu; Si, Lou-Bin; Wang, Xiao-Jun; Long, Xiao; Liu, Yi-Fang
Abstract: Photodynamic therapy (PDT) is a new therapy for treating cancer with less toxicity, high selectivity, good cooperativity, and repetitive usability. However, keloid treatment by PDT is mainly focused on clinical appearance, and few studies have been conducted on the mechanisms of PDT. In this study, key factors of the classical mitochondrial apoptosis signaling pathway were measured to assess the effect of a new PDT photosensitizer (p1). A specific inhibitor of caspase-8 (Z-IETD-FMK) was also used to verify the possible mechanisms. Twelve samples were obtained from 12 patients (six with keloids and six without) selected randomly from the Department of Plastic Surgery at Peking Union Medical College Hospital from January to December 2020. After cell culture, fibroblasts were divided into 13 groups. The morphology of fibroblasts in each group was observed by microscopy. Cell activity was measured by cell counting kit-8, and cell apoptotic morphology was observed by TUNEL staining. The reactive oxygen species (ROS) relative value was measured by a ROS test kit. The expression levels of key mitochondrial factors (caspase-3, caspase-8, cytochrome-c, Bax, and Bcl-2) were assessed by western blot, and mRNA expression of caspase-3 and caspase-8 was measured by RT-qPCR. We showed that p1 had a satisfactory proapoptotic effect on keloid fibroblasts by increasing the expression of ROS, caspase-3, caspase-8, and cytochrome-c, and decreasing the Bcl-2/Bax ratio; however, this effect was partially inhibited by Z-IETD-FMK, indicating that caspase-8 may be one of the p1's targets to achieve the proapoptotic effect.